Pendidikan Multikultural sebagai Pilar Dasar-Dasar Kependidikan di Era Globalisasi - Gihna Zahra; Lula Pebriani; Nabila Rhamadani; Gusmaneli (ALADALAH: Jurnal Politik, Sosial, Hukum dan Humaniora, 2026)
Globalization accelerates cross-cultural interactions and deepens social plurality, compelling education to move beyond knowledge transmission toward shaping learners capable of engaging constructively with diversity. Multicultural education emerges as a strategic framework for fostering tolerance, empathy, and intercultural competence. This literature-based inquiry analyzes the relevance of multicultural education in addressing global challenges, its integration within curriculum structures, and the role of teachers in cultivating inclusive learning environments. The analysis reveals that multicultural education significantly strengthens social cohesion, enhances learners’ awareness of diversity, and promotes the development of critical and collaborative character traits. These findings highlight the urgency of mainstreaming multicultural values in educational policy and practice to support a harmonious social order amid global dynamics.